Risk-Return Analysis of Infosys Co. Ltd - Das, Pradip Kumar (Archives of Business Research, 2025)
This research paper presents a comprehensive risk-return analysis of Infosys Co. Ltd., an Indian multinational IT corporation, using historical monthly returns from January 2021 to December 2024. Amidst economic volatility and globalization, assessing the company's return profile and embedded risk is crucial for reasoned investment decisions and management. The study employs empirical models including descriptive statistics, Monte Carlo simulation, multivariate regression, Value at Risk (VaR), and Conditional Value at Risk (CVaR) to assess Infosys' investment charisma and volatility. Results reveal that Infosys has consistently generated moderate volatility returns, maintaining favorable risk-adjusted profile. Analysis confirms Infosys as a viable long-term investment within diversified portfolios, while advising caution in extreme market scenarios. It particularly benefits investors seeking exposure to the Indian IT sector with rational perspective on associated risks. Integrating classical and advanced simulation models, visualizations, and comparative forecasts, the study serves as practical guidance for investors, analysts, and researchers in risk-return evaluation and portfolio management.